Wizerunek twórczego pedagogicznie nauczyciela klas I-III - Magda-Adamowicz, Marzenna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Pedagogical creativity of a teacher is indispensable, not only in his personal and professional development, but also in the development of his pupils. It is him who represents an example to follow, shows ways and methods of activating creative attitudes.
Keywords: nauczyciele nauczania początkowego; pedagogika; twórczość; praca; socjologia i społeczeństwo; metoda; Polska; od 1989 r.